(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
Linux namespaces and control groups (cgroups) are key kernel primitives that enable lightweight virtualization by creating isolated environments called containers. These containers share the host kernel while maintaining process isolation and resource control, providing a balance between traditional hypervisor-based virtualization and bare-metal deployment. This paper examines the architecture, isolation mechanisms, and performance characteristics of namespaces and cgroups. We highlight how these features form the foundation of popular container technologies such as Docker and LXC, and compare their efficiency and isolation properties with conventional virtualization approaches.